Práticas de cuidado do enfermeiro a pessoas com hipertensão arterial sistêmica: perspectiva cultural - Rosso, Laís Fuzer (2017)
The research in question had as object of study the care practices of the nurses of the Family Health Strategy to people with a diagnosis of Systemic Arterial Hypertension. As a guiding question: how do Family Health Strategy nurses develop care practices for people diagnosed with systemic arterial hypertension, according to the cultural perspective? From this, the general objective was to know the care practices performed by the nurses of the Family Health Units to people with a diagnosis of systemic arterial hypertension under the cultural perspective. Research with a qualitative, exploratory-descriptive approach that had as a study scenario the Family Health Units in a municipality in the interior of Rio Grande do Sul, Brazil. Participants were nurses who held positions in the research setting. Data were collected from March to August of 2016 through a semi-structured interview and non-participant systematized observation. For the data analysis, Minayo's Operative Proposal was used. The research followed the ethical principles of Resolution number 466/2012. The results were organized into two categories: "because each user is one": the cultural diversity in nurses' practices of care for the person with systemic arterial hypertension and "... but much more than that we can not do": to limit and judge the present in the practices of nurse care the person with systemic arterial hypertension, in which they discussed the cultural diversity and limitations present in the practices of care of the nurse to people with systemic arterial hypertension. Regarding cultural diversity, it was evident that nurses practice their practices based on a vision of the environmental context, as well as on the singularity, knowledge and valorization of the knowledge that the user brings with it, enabling care that is more in keeping with their reality. The practices of care and feeding were also discussed; it was evidenced that the eating habits is a cultural aspect very present in the daily life of the person with hypertension, however there are negotiations and adaptations that can be carried out between the person and the nurse, for the best prognosis of the disease. Another practice of care addressed was the non prioritization of care to the person with systemic arterial hypertension, choosing areas such as women's and child's health as the nurse's focus. It was also evidenced, the professional's lack of time and the immutable cultural pattern of the person with hypertension. Thus, in order to develop care practices, it is fundamental to recognize the presence of the culture, permeating the care of chronic illness, as well as the appreciation of its presence. Nursing care practices can be guided by Madeleine Leininger's Theory of Diversity and Cultural Universality of Care in order to support and facilitate care for users diagnosed with systemic arterial hypertension